2021
DOI: 10.48084/etasr.4202
|View full text |Cite
|
Sign up to set email alerts
|

Attack Detection in IoT using Machine Learning

Abstract: Many researchers have examined the risks imposed by the Internet of Things (IoT) devices on big companies and smart towns. Due to the high adoption of IoT, their character, inherent mobility, and standardization limitations, smart mechanisms, capable of automatically detecting suspicious movement on IoT devices connected to the local networks are needed. With the increase of IoT devices connected through internet, the capacity of web traffic increased. Due to this change, attack detection through common method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 35 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The results showed that the SLFN classification approach outperformed other classification algorithms. Maryam et al [75] proposed that three ML algorithms RF, GDBT, and SVM were applied to the NSL-KDD dataset using binary classification. The results showed that the RF obtained the highest accuracy on the fog layer while SVM obtained lowest accuracy.…”
Section: Analysis and Comparison Of Supervised ML Algorithms For Iot ...mentioning
confidence: 99%
“…The results showed that the SLFN classification approach outperformed other classification algorithms. Maryam et al [75] proposed that three ML algorithms RF, GDBT, and SVM were applied to the NSL-KDD dataset using binary classification. The results showed that the RF obtained the highest accuracy on the fog layer while SVM obtained lowest accuracy.…”
Section: Analysis and Comparison Of Supervised ML Algorithms For Iot ...mentioning
confidence: 99%
“…Based on machine learning, Anwer et al [16] developed a framework for detecting attacks in network flow. Their framework used three widespread machine learning classifiers: a Support Vector Machine (SVM), Gradient Boosted Decision Trees (GBDT), and RF.…”
Section: Anomaly-based Intrusion Detection Systems (Ads) Related Workmentioning
confidence: 99%
“…Further, this model is en-hanced with the Seagull Adopted Elephant Herding optimization (SAEHO) model to tune the weights for better detection. Anwer et al [4] evaluated the ML-based approaches for malicious traffic attack detection. It used three approaches Support vector machine (SVM), Gradient boosted decision trees (GB-DT), and Random forest (RF) for attack detection in IoT.…”
Section: Related Workmentioning
confidence: 99%